Perception and attitudes of local communities towards vertebrate fauna in the Andes of Colombia: Effects of gender and the urban/rural setting - Moreno-Rubiano, Maria Camila; Moreno-Rubiano, Juan Diego; Robledo-Buitrago, Daniel; De Luque-Villa, Miguel Antonio; Urbina-Cardona, J. Nicolas; Granda-Rodriguez, Hernan Dario (Ethnobiology and Conservation, 2023)
This study sought to evaluate the perception and attitudes of the inhabitants of an Andean region of Colombia towards 17 native terrestrial vertebrate species and their relationships with sociodemographic factors such as gender and locality (town or country). Data were collected through semi-structured surveys of 100 participants. Five variables measuring people’s perceptions (level of liking, medicinal use, detrimental to daily activity, disease transmission, and folklore traditions) were statistically evaluated using a Likert scale ranging. To measure attitudes, respondents were asked whether they would agree that the government should protect or eradicate some of the species in the region. The respondents’ level of liking and their folklore (legend and myth-type superstitions) only varied for the owl between town and country. Native rat, bat, and snake species had the highest frequency of negative perceptions among people that varied according to locality and gender, in contrast to birds such as the canary and hummingbird species where positive perceptions predominated. The species that presented the greatest diversity of folklore traditions were owl, snake, and the bat species, all mainly associated with death and bad luck. Most respondents considered conserving all species, with a preference for birds and some mammals and reptiles. However, they considered eliminating species such as native rat, snake, and bat species from the region. Wildlife conservation initiatives must understand people’s perceptions for using charismatic species, while implementing awareness campaigns on the ecological importance of species that are less liked by local communities. We discussed local people’s perceptions and medicinal uses of wildlife species.